Long-term effect of specific treatment of primary aldosteronism on carotid intima–media thickness. Issue 4 (April 2015) - Holaj, Robert; Rosa, Ján; Zelinka, Tomáš; Štrauch, Branislav; Petrák, Ondřej; Indra, Tomáš; Šomlóová, Zuzana; Michalský, David; Novák, Květoslav; Wichterle, Dan; Widimský, Jiří
<x xml:space="preserve">Abstract</x> Background: Aldosterone has been shown to substantially contribute to the accumulation of different types of collagen fibres and growth factors in the arterial wall, thus increasing wall thickness. A previous study showed reduction of increased common carotid intima–media thickness (IMT) in patients with primary aldosteronism 1 year after adrenalectomy. Our study in patients with primary aldosteronism was aimed at comparing the long-term effect of adrenalectomy vs. spironolactone therapy on common carotid IMT regression. Method: Forty-two patients with confirmed primary aldosteronism (21 with aldosterone-producing adenoma treated by unilateral laparoscopic adrenalectomy, 21 treated with spironolactone) were investigated by carotid ultrasound at baseline and 1 and 6 years after the specific treatment. Results: There was a decrease in common carotid IMT from 0.956 ± 0.140 to 0.900 ± 0.127 mm (−5.9%; P < 0.05) at 1 year and to 0.866 ± 0.130 mm (−9.4%; P < 0.01) at 6 years after adrenalectomy; in the spironolactone group, common carotid IMT decreased from 0.917 ± 0.151 to 0.900 ± 0.165 mm (−1.8%; NS) at 1 year and to 0.854 ± 0.176 mm (−6.8%; P < 0.01) at 6 years of treatment. The magnitude of improvement at 1 year was significantly higher (by 70%; P < 0.05) in the adrenalectomy group; however, the difference (by 27%) became nonsignificant at 6 years. Comparing the adrenalectomy and spironolactone groups, there was no significant difference in blood pressure decrease after treatment. Conclusion: In the long term, spironolactone therapy in patients with primary aldosteronism had significant effect on regression of IMT, which was comparable to surgical treatment in patients with unilateral forms of primary aldosteronism.